Survival and recurrence patterns of multifocal glioblastoma after radiation therapy - Syed, Mustafa; Liermann, Jakob; Bernhardt, Denise; Bougatf, Nina; Paul, Angela; Rieken, Stefan; Debus, Jürgen; Adeberg, Sebastian (Cancer management and research, 2018)
Survival and recurrence patterns of multifocal glioblastoma after radiation therapy Mustafa Syed,1–3 Jakob Liermann,1–3 Vivek Verma,4 Denise Bernhardt,1,2 Nina Bougatf,1,3 Angela Paul,1,2 Stefan Rieken,1–3 Jürgen Debus,1–3,5 Sebastian Adeberg1,2,5 1Heidelberg Institute of Radiation Oncology, Im Neuenheimer Feld 400, 69120 Heidelberg, Germany; 2Department of Radiation Oncology, University Hospital Heidelberg, Im Neuenheimer Feld 400, 69120 Heidelberg, Germany; 3Heidelberg Ion-Beam Therapy Center (HIT), Im Neuenheimer Feld 450, 69120 Heidelberg, Germany; 4Department of Radiation Oncology, University of Nebraska Medical Center, Omaha, NE 68198, USA; 5Clinical Cooperation Unit Radiation Oncology, German Cancer Research Center (DKFZ), Im Neuenheimer Feld 280, 69120 Heidelberg, Germany Purpose: It is hypothesized that multifocal glioblastoma (mGBM) is associated with worse prognosis compared to unifocal disease (uGBM). This study aims to investigate the differences in survival rates and progression patterns of patients between these two groups after radiation therapy. Patients and methods: We retrospectively analyzed 265 patients with primary GBM undergoing radiation therapy at the Department of Radiation Oncology, University Hospital Heidelberg, Germany, between 2004 and 2013. Of these, 202 (76%) were uGBMs and 63 (24%) were mGBMs. First, progression-free survival (PFS) and overall survival (OS) between groups were compared using the Kaplan–Meier method. Second, univariate and multivariate Cox proportional hazards regression was applied to discern prognostic and predictive factors with PFS and OS in the cohorts. Third, recurrence patterns of uGBMs and mGBMs were assessed on follow-up MRIs and compared using the chi-squared test. Results: As compared to patients with uGBM, patients with mGBM experienced significantly worse median OS (11.5 vs 14.8 months, P=0.032). Overall, 195 (73.0%) patients experienced tumor progression: 153 (75.7%) patients with uGBM and 46 (73.0%) patients with mGBM. There were no significant differences in PFS between the respective groups (6.5 vs 6.6 months, P=0.750). Of note, concomitant temozolomide treatment was associated with an OS benefit in both uGBM and mGBM by about five months (P=0.006 and P<0.001). Furthermore, there were no significant differences in progression patterns of uGBM and mGBM. Both recurred as unifocal and multifocal disease (P=0.51), and local vs distant brain recurrences occurred similarly in both groups (OR=1.33, P=0.53). Conclusion: Multifocality is an independent predictor of survival in GBM. Concomitant temozolomide treatment improved OS of patients with mGBM and uGBM. Both disease types showed similar patterns of progression. Current target volume concepts seem to be adequate in both unifocal and multifocal GBMs. GBM, the most common primary brain tumor in adults, is associated with poor survival. We show herein that multifocality is an independent prognostic factor for survival. We also illustrate that the progression patterns of both unifocal and multifocal GBM are similar.Keywords: temozolomide, chemotherapy, progression, multifocal, glioblastoma, gliomatosis, high grade glioma, target volume
Gesehen am 02.05.2019